Large eddy simulation on using a cavity-jet controller for supersonic blunt base mixing layer control. (August 2019) - Zhou, Yong-yi; Yang, Rui; Zhao, Yu-xin
Abstract: In this study, a cavity-jet controller was used to control the supersonic blunt base mixing layer. This method is simple in structure, requires no external energy, and can utilize the pressure potential energy of the flow. A large eddy simulation was performed to numerically investigate the control effect. The Mach numbers of the upper and lower layers were 1.5 and 2.5, respectively, and the convective Mach number was 0.35. The simulation flow field structures and mean properties with and without the cavity-jet controller were compared. The results showed that this controller enhanced the turbulence intensity of the flow. The mixing thickness was used to quantify the mixing characteristics. The controller significantly improved the mixing performance. The flow fields were monitored at several points to record the pressure pulsation information, and the power spectral density was analyzed. Highlights: A cavity-jet controller was developed to control supersonic mixing layer. The method has a simple structure and requires no external energy. LES was performed to evaluate the effects of the controller. Power spectral density (PSD) method was adopted to interpret the mechanism of the controller. The results showed that the controller can enhance the mixing efficiency.